2022
DOI: 10.1039/d1nj05967j
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and growth mechanism of dendrite-free Ni–Cu catalysts by magneto-electrodeposition for the hydrogen evolution reaction

Abstract: Developing high-efficiency electrocatalysts for hydrogen evolution reaction (HER) is of great importance. In this paper, dendrite-free Ni-Cu catalysts were synthesised via one-step pulse electrodeposition under a weak magnetic field (0.5...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…During electrodeposition, phenomena like uneven deposition, aggregation, overgrowth, and two-dimensional unilateral growth are inevitable, leading to hindered enhancement of electrocatalytic activities. [145] To solve these issues, Li et al [146] synthesized a non-dendrite Cu-Ni catalyst by one-step pulsed electrodeposition coupled with a weak magnetic field of 0.24 T. Regardless of the direction of the magnetic field, the reactants are influenced by MHD effects, extensively promoting the mass transfer capacity and dispersion uniformity, as well as inhibiting agglomeration during electrodeposition. The electrochemical results demonstrate the formation of Ni-Cu catalysts with more exposed specific surface area, thereby significantly enhancing activity requiring only 57 mV at a current density of 10 mA cm −2 .…”
Section: Magnetic Field-assisted Electrodepositionmentioning
confidence: 99%
“…During electrodeposition, phenomena like uneven deposition, aggregation, overgrowth, and two-dimensional unilateral growth are inevitable, leading to hindered enhancement of electrocatalytic activities. [145] To solve these issues, Li et al [146] synthesized a non-dendrite Cu-Ni catalyst by one-step pulsed electrodeposition coupled with a weak magnetic field of 0.24 T. Regardless of the direction of the magnetic field, the reactants are influenced by MHD effects, extensively promoting the mass transfer capacity and dispersion uniformity, as well as inhibiting agglomeration during electrodeposition. The electrochemical results demonstrate the formation of Ni-Cu catalysts with more exposed specific surface area, thereby significantly enhancing activity requiring only 57 mV at a current density of 10 mA cm −2 .…”
Section: Magnetic Field-assisted Electrodepositionmentioning
confidence: 99%
“…Currently, one-dimensional metal nanocatalysts are primarily prepared by deposition, which requires bonding using adhesives such as Teflon and Nafion, resulting in a product that is easy to shed and has low electrical conductivity. To overcome these issues, Li 27 synthesized a Ni–Cu catalyst by electrodeposition under a magnetic field (0.5 T), which significantly promoted the mass transfer of the catalyst under the influence of the magnetohydrodynamic (MHD) effect. Cai 28 used a straightforward method that involved applying a magnetic field to facilitate the growth of Ni nanochain cores, which provided a large surface area for the subsequent vertical growth of few-layered NiFe layered double hydroxide (LDH) nanosheets.…”
Section: Magnetic Field-engineered Catalyst Synthesismentioning
confidence: 99%
“…The external magnetic field produces Lorentz force, which affects the mass transfer rate of ferromagnetic Ni 2+ and diamagnetic Cu 2+ , and also changes the nucleation mode of NiCu. It was found that NiCu nucleation gradually changed from progressive nucleation to instantaneous nucleation under a vertical magnetic field of 0.5 T. 22 This might be due to the Lorentz force generated by the coupling of the magnetic and electric fields which would cause NiCu deposition to change from dendritic crystal structures to small-sized clusters (90 nm). 26 The uniform distribution of Ni and Cu elements in NiCu substrates prepared under a magnetic field of 0.5 T was found by EDS, which proved that NiCu substrates were successfully prepared (Fig.…”
Section: Morphological and Structural Characterizationmentioning
confidence: 99%
“…21 The external magnetic field could improve the dispersion rate of NiCu particles on the cathode surface and increase the active specific surface area. 22 In a previous work, 23 we successfully prepared fine and CoFe particles uniformly deposited on Si (100) substrates containing Ni sub-crystal layers using a uniform gradient magnetic field assisted electrodeposition method. It was noted that the applied magnetic field strength was too high during the electrodeposition process, and therefore, the deposit tended to form dendritic crystalline structures.…”
Section: Introductionmentioning
confidence: 99%